Lemon Aromatherapy on Lowering Blood Pressure in Elderly with Hypertension - Riandi Alfin; Destiani Rahma R; Sitti Syabariyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effectiveness of lemon aromatherapy in reducing blood pressure in the elderly with Hypertension. The research method was a quick experiment with a pretest-posttest design with a control group. The Independent T-test study showed that the average systolic blood pressure in the intervention group was 138, while in the control group, it was 153. In addition, the moderate diastolic blood pressure in the intervention group was 82.80, while in the control group, it was 93.67. The results of statistical tests showed differences in the mean systolic and diastolic blood pressure in the control and intervention groups (p=0.000). In conclusion, lemon aromatherapy can reduce blood pressure in older people with Hypertension. Keywords: Lemon Aromatherapy, Hypertension, Blood pressure